Assessment of microplastic pollution in the aquatic ecosystems – An indian perspective - Kumar Raja Vanapalli (Case Studies in Chemical and Environmental Engineering, 2021)
Microplastics (MPs) are ubiquitous in the aquatic environment due to plastic waste proliferation in diverse sectors. The recent years have witnessed exponential growth in the number of studies focusing on their occurrence, distribution and toxicity in several parts of India. The overarching aim of this article is to evaluate the sources, abundance, and characteristics of MPs reported in the sediments, water, and biota of the aquatic ecosystems in India. The review revealed that while the MPs from land-based sources such as littering, domestic sewage, and industrial runoff were carried by rivers and streams, MPs from other sources including marine litter and accidental spillages during shipping directly enter the aquatic environment. The unique hydrodynamic conditions during the southwest and northeast monsoons were found to influence the abundance and distribution of MPs in the Indian aquatic ecosystems. Although the seaward flushing and monsoonal flux were reported to increase the abundance of MPs, the reversal of the winds and currents during the NE monsoon was observed to oppose the drift of MPs towards the Goa coast. The reported higher concentrations of MPs in the beach sediments collected from the high tide line (1323 ​± ​1228 ​mg/m2) as compared to that of low tide line (178 ​± ​261 ​mg/m2) along the southeast coast of India also emphasize the tidal influence. While the shape and type of MPs can help in determining their sources, their size and colour might influence their ingestion in aquatic biota and also indicate the amount of degradation. The variability in the characteristics of MPs observed between different studies could also be a factor of difference in the sampling and analysis techniques adopted. Although the general practice of degutting before consumption could lower the risk of MPs transfer from fish, popular delicacies of dried fish and shrimps could be potential sources of human ingestion. Since the research was mostly confined to the southern coasts of India and some urban recreational beaches, the MP pollution on other coastal regions of India remains largely unexplored. Moreover, with very few studies reporting on the MP pollution in the freshwater ecosystems, the wide network of rivers and enclosed water bodies could also be the major focus of future research.